Exciton and polaron dynamics in polymeric semiconductors: The influence of interchain order. - Silva, C; Herz, L; Daniel, C (2003)
The importance of interchain order in exciton and polaron dynamics in poly-6,6′, 12, 12′-tetraalkyl-2, 8-indenofluorene (PIF), the blue-emitting semiconductor conjugated polymer for optoelectronics was described. The femtosecond transient photoluminescence (PL), femtosecond transient absorption and quasi-steady-state photoinduced absorption spectroscopy were used for this study. It was concluded that the triplet generation yield is strongly dependent on order, with the disordered material displaying a higher yield.